The impact of maternal diet fortification with lipid‐based nutrient supplements on postpartum depression in rural Malawi: a randomised‐controlled trial. Issue 2 (5th April 2016) - Stewart, Robert C.; Ashorn, Per; Umar, Eric; Dewey, Kathryn G.; Ashorn, Ulla; Creed, Francis; Rahman, Atif; Tomenson, Barbara; Prado, Elizabeth L; Maleta, Ken
Abstract: Perinatal depression is highly prevalent in low‐and‐middle‐income countries and has been linked to poor child health. Suboptimal maternal nutrition may be a risk factor for perinatal depression. In this randomised‐controlled trial conducted in rural Malawi, we set out to test the hypothesis that women taking a fatty acid‐rich lipid‐based nutrient supplement (LNS) would have fewer depressive symptoms postpartum than those taking iron‐folate (IFA) or multiple‐micronutrient (MMN) capsules. Women were recruited from antenatal clinics and randomised to receive LNS or MMN during pregnancy and for 6 months postpartum, or IFA during pregnancy only. Maternal depressive symptoms were measured using validated translations of the Self Reporting Questionnaire (SRQ) and Edinburgh Postnatal Depression Scale (EPDS), antenatally (SRQ only) and at 6 months postpartum (SRQ and EPDS). Analysis was by modified intention to treat. One thousand three hundred and ninety one women were randomised (LNS = 462, MMN = 466, IFA = 463). The groups were similar across a range of baseline variables. At 6 months postpartum, 1078 (77.5%) had SRQ completed; mean (SD) scores were LNS 1.76(2.73), MMN 1.92(2.75), IFA 1.71(2.66), P = 0.541. One thousand and fifty seven (76.0%) had EPDS completed; mean (SD) scores were LNS 5.77(5.53), MMN 5.43(4.97), IFA 5.52(5.18), P = 0.676. There were no statistically significant differences between the groups on SRQ or EPDS scores (continuous or dichotomised) in unadjusted or adjusted models. In conclusion, fortification of maternal diet with LNS compared with MMN or IFA did not reduce postnatal depressive symptoms in this study.